167k views
3 votes
X² - 6x – 40=0
Complete the square

User Waruyama
by
5.1k points

1 Answer

1 vote

Answer:

Explanation:

x^2 - 6x - 40 = 0.....get the -40 to the other side

x^2 - 6x = 40....now take half of ur x term (6)....so its 3...then square it (3^2 = 9)...now add 9 to both sides

x^2 - 6x + 9 = 40 + 9

(x - 3)(x - 3) = 49

(x - 3)^2 = 49...take sqrt of both sides, eliminating the ^2

x - 3 = sqrt 49

x = 3 (+ - ) 7

x = 3 + 7 = 10 or x = 3 - 7 = -4

so x = 10 or x = -4

User Legotin
by
5.6k points